Incorporation of the UN Convention on the Rights of the Child in National Law - Simon Hoffman (The International Journal of Children’s Rights, 2020)
Incorporation is amongst the legislative measures of implementation of the UN Convention on the Rights of the Child (CRC) recommended by the Committee on the Rights of the Child. This article will discuss incorporation of the CRC in national law. It will show how incorporation is understood in different contexts, and highlight possible tensions between child rights and international law discourse and analysis. It begins by reviewing literature on incorporation of human rights treaties before discussing how incorporation is conceptualised in the context of the CRC. The focus then shifts to a review of studies that provide insights into how incorporation and legal integration of the CRC impact on how children’s rights are treated in national legal systems. While primarily a commentary on the available literature the authors reflect on the significance of incorporation and how this is understood for academic and legal analysis, and what the evidence tells us about its contribution to the realisation of children’s rights.